Emotional Intelligence Positively Affects Student's Social Skills in Physical Education - Dicky Tri Juniar; Adang Suherman; Beltasar Tarigan; Agus Mahendra (Kinestetik, 2023)
The social skills of teenagers, especially those of high school age, are very concerning. Numerous pieces of evidence point to the existence of social issues that manifest themselves not only in the context of the educational institution but also in the wider society. Lack or low emotional intelligence is considered the presence of disturbances in emotional and social functioning. Social skills and managing emotions are essential to blocking problematic behaviors. But empirical evidence of emotional intelligence and its influence on social skills is minimal. This study aims to prove the influence of emotional intelligence on students' social skills at the High School level. This research uses a descriptive method with a correlational type of research. The population used in this study was all high school students in the Tasikmalaya area, and as many as 173 students were sampled in this study by random cluster sampling. The data analysis was a simple linear regression test using IBM SPSS 26. The result of this study is the relationship between variables of 0.503 in a positive direction, with a coefficient of determination (R Square) of 0.253, which means that free variables have an influence of 25.3% on bound variables. Referring to the calculated F value = 57.967 with a Sig. rate of 0.000 < 0.05 means that the null hypothesis is rejected, and the research hypothesis is accepted. In conclusion, emotional intelligence positively affects students' social skills in Physical Education.